Universal fixed‐point digital controller for control theory studies. Issue 5 (12th January 2021) - Sanchez, Alberto; de Castro, Angel; Benedicto, Jorge; Martínez‐García, María Sofía
Abstract: The laboratories of control theory are often limited to simulations and a few or none experimental tests. As in other technical subjects, practical experiments really help to understand the theory but need much time and the experimental platforms are usually expensive. This paper describes a platform that implements a universal third‐order discrete controller based on field programmable gate array (FPGA). The controller is implemented using fixed‐point arithmetic, with 17‐bit coefficients, but students can reduce the number of bits to find the resolution problems that may arise. This low‐cost platform, based on a Xilinx Spartan FPGA, allows students to try controllers just by configuring the coefficients of the controller through a computer application and a USB port. It drastically reduces the implementation time, allowing more time for design and testing. Therefore, students can try many controllers in the same laboratory session so that they can check experimentally their behavior in real prototypes and see the differences between simulations and physical systems. This platform has been applied in a real course over two academic years. The student opinion survey shows that the survey respondents consider the platform useful for more deeply understanding the subject, with an average score of 4.47/5.00 on a Likert scale (with a margin of error of 15.56% with a 95% confidence level). Besides this, the platform records the usage statistics showing that there is a relationship between the application usage and the marks in both the theory and laboratory parts.